Quantifying the Carbon Stocks in Urban Trees: The Rio de Janeiro Botanical Garden as an Important Tropical Carbon Sink - Bruno Coutinho Kurtz; Thaís Moreira Hidalgo de Almeida; Marcus Alberto Nadruz Coelho; Lara Serpa Jaegge Deccache; Ricardo Maximo Tortorelli; Diego Rafael Gonzaga; Louise Klein Madureira; Ramon Guedes-Oliveira; Claudia Franca Barros; Marinez Ferreira de Siqueira (Journal of Zoological and Botanical Gardens)
The rapid urbanization process in recent decades has altered the carbon cycle and exacerbated the impact of climate change, prompting many cities to develop tree planting and green area preservation as mitigation and adaptation measures. While numerous studies have estimated the carbon stocks of urban trees in temperate and subtropical cities, data from tropical regions, including tropical botanic gardens, are scarce. This study aimed to quantify the aboveground biomass and carbon (AGB and AGC, respectively) stocks in trees at the Rio de Janeiro Botanical Garden arboretum, Rio de Janeiro, Brazil. Our survey included 6793 stems with a diameter at breast height (DBH) ≥ 10 cm. The total AGB was 8047 ± 402 Mg, representing 4024 ± 201 Mg of AGC. The AGB density was 207 ± 10 Mg·ha−1 (AGC = 104 ± 5 Mg·ha−1), which is slightly lower than the density stored in Brazil’s main forest complexes, the Atlantic and Amazon forests, but much higher than in many cities worldwide. Our results suggest that, in addition to their global importance for plant conservation, tropical botanic gardens could function as significant carbon sinks within the urban matrix.